Upper and Lower Slight $α(τ_1,τ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the notions of upper and lower slightly $α(τ_1,τ_2)$-continuous multifunctions. Furthermore, several characterizations of upper and lower slightly $α(τ_1,τ_2)$-continuous multifunctions are discussed.
Keywords: $α(τ_1,τ_2)$-open set; upper slightly $α(τ_1,τ_2)$-continuous multifunction; lower slightly $α(τ_1,τ_2)$-continuous multifunction